Avtor je mrtev. Naj živi avtor! - Troha, Gašper (Primerjalna književnost, 2009)
Although the 1960s and 1970s brought about explicit declarations of the death of the author (Barthes) and sought other concepts to replace it (e.g. authorial function of Michel Foucault), the author survived. Where does our inability to locate and define an author of literature come from? My hypothesis is that an answer can be found through analysis of a heterogeneous nature of our subject, to be more precise in an analysis of its two roles - an empirical author and an author as a function who is, according to Foucault, located on the threshold of a text or a discourse. The paper deals with two autobiographical texts by the Slovene writer Lojze Kovačič - descriptions of the author''s experiences in primary school as he described them in novels Basel and Otroške stvari (Childish things).
Keywords: Kovačič, Lojze, 1928-2004; literarna teorija; literary theory; avtor; avtorstvo; autobiography; avtobiografija; avtobiografska literatura